Dor neuropática em pacientes com doença falciforme: estudo transversal avaliando adolescentes e adultos jovens - Vasconcelos, Hulemar Andrade (2017)
Abstract Chronic pain conditions are little studied and may be under estimated in sickle cell disease (SCD). The aim of this study was to identify the occurrence and characteristics of neuropathic pain (NP) in SCD patients. A sample of 56 patients was chosen from a total of 554 patients submitted to the inclusion criteria between 2015 and 2016. The Leeds assessment of neuropathic symptoms and signs scale was used for detectingNP.The groups with and without NP were compared by sex, age, use of hydroxyurea, and sensory changes through Chi-square, Fisher’sexact, ANOVA, and Kruskal-Wallistests. The average age was 20.6 years (SD ± 4.6), 51.8% of the patients were male, and 14 patients (25%) suffered from NP. Most commonly, the pain was reported to be in the lower back area (53.6%). Age was positively related to NP: the average age in the group with NP was 22.7years (SD±4.1) and in the group without NP was 19.8 years (SD±4.5), p<0.05. Higher rates of NP occurred in patients aged 19 years or older, compared with that in teens (p < 0.01). There was a positive association between NP and the use of hydroxyurea (p < 0.05). An association was found between NP and sensitive neurological changes (p < 0.01). Therefore, screening for NP may result in faster and more effective diagnoses and consequently initiate appropriate treatment.